The Value of CHSE Hotel Certificates in Increasing Hotel Loyalty among Domestic Tourists - Imam Nur Hakim; Muhammad Iqbal Rosyidi; Faisyal Faisyal (Universitas Muhammadiyah Yogyakarta, 2023)
The COVID-19 pandemic remains, and its impact continues to collapse on Indonesian tourism, particularly the hotel industry. During the pandemic, the Ministry of Tourism and Creative Economy implemented a program of issuing CHSE certificates to the hotels in order to restore their performance. However, no market-based analysis has determined the impact of the hotel's CHSE certification. This research measures how the CHSE certification can increase Indonesian tourists' loyalty to hotels during a pandemic. The structural equation model (SEM) found a significant positive influence on Indonesian tourists' loyalty from 564 respondents. Variables such as perceived quality, image, trust, perceived value, and satisfaction significantly influenced Indonesian tourist loyalty toward CHSE-certified hotels during the pandemic, both directly and indirectly. The NFI score of 0.907 indicates that the model constructed in this study is highly sufficient to describe the loyalty of CHSE-certified hotel visitors during the pandemic.